The Impact of Ischemic Stroke on Gray and White Matter Injury Correlated With Motor and Cognitive Impairments in Permanent MCAO Rats: A Multimodal MRI-Based Study - Yang, Le; Li, Manzhong; Zhan, Yu; Feng, Xuefeng; Lu, Yun; Li, Mingcong; Zhuang, Yuming; Lei, Jianfeng; Zhao, Hui (Frontiers in Neurology, 2022)
Background: Identifying the alterations of the cerebral gray and white matter is an important prerequisite for developing potential pharmacological therapy for stroke. This study aimed to assess the changes of gray and white matter in rats with focal cerebral ischemia using magnetic resonance imaging (MRI), and to correlate them with the behavior performance. Methods: Rats were subjected to permanent middle cerebral artery occlusion (MCAO) or sham surgery and reared for 30 days. Motor and cognitive function of the rats were examined by gait and Morris water maze (MWM) tests respectively. Multimodal MRI was conducted to examine the functional and structural changes of the gray and white matter followed with luxol fast blue (LFB) staining. Results: The gait and MWM tests revealed significant motor and cognitive dysfunction in MCAO rats respectively. Magnetic resonance angiography presented abnormal intracranial arteries in MCAO rats with reduced signal intensity of the anterior cerebral artery, anterior communicating cerebral artery, internal carotid artery. and increased signal intensity of basilar artery compared with sham rats. Arterial spin labeling confirmed the decreased cerebral blood flow in the infarcted sensorimotor cortex and striatum. Structural T2-weighted imaging and T2 mapping showed brain atrophy and elevation of T2 value in the gray (sensorimotor cortex, striatum) and white (external capsule, internal capsule) matter of MCAO rats. The results from diffusion tensor imaging (DTI) corresponded well with LFB staining showing reduced relative FA accompanied with increased relative AD and RD in the gray and white matter of MCAO rats compared with sham rats. Fiber tracking derived from DTI further observed significantly reduced fiber density and length in the corresponding brain regions of MCAO rats compared with sham rats. Specially, the DTI parameters especially FA in the relevant gray matter and white matter significantly correlated with the behavior performance in the gait and MWM tests. Conclusions: Collectively, our study demonstrated that both the gray and white matter were severely impaired in MCAO rats and DTI alterations of the gray and white matter, particularly the FA, might be favorable predictors of poststroke motor and cognitive impairments.